2019
DOI: 10.15713/ins.clever.34
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic macular holes – A review of current management strategies

Abstract: Description of the Condition Macular holes (MHs) are retinal defects which involve the center of the anatomical fovea. [1,2] Severity may range from asymptomatic incidentally discovered MHs, to advanced vision-threatening ones. [2,3] MHs are often described according to the extent of retinal layers involvement. Full-thickness MHs (FTMHs) encompass all the layers of the retina from the internal limiting membrane (ILM) to the retinal pigmented epithelium (RPE) [Figure 1]. [2] Partialthickness MHs, also termed la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…[7,12,13,15,16] It has been suggested that while idiopathic MH (IMH) formation is related to chronic traction, TMHs are the result of acute traction forces on the macula. [1,12,13] However, in contrast to IMHs, a significant portion of TMH cases (10-67% according to different reports) may resolve spontaneously. [7,17] Therefore, observation before any intervention is a reasonable option for many patients.…”
Section: Traumatic Mhs (Tmhs)mentioning
confidence: 99%
See 3 more Smart Citations
“…[7,12,13,15,16] It has been suggested that while idiopathic MH (IMH) formation is related to chronic traction, TMHs are the result of acute traction forces on the macula. [1,12,13] However, in contrast to IMHs, a significant portion of TMH cases (10-67% according to different reports) may resolve spontaneously. [7,17] Therefore, observation before any intervention is a reasonable option for many patients.…”
Section: Traumatic Mhs (Tmhs)mentioning
confidence: 99%
“…Macular holes (MHs) are full thickness retinal defects involving the anatomical fovea. [1] The first staging system for MHs was described by Gass in 1988. [1,2] The use of optical coherence tomography (OCT) led to the development of newer staging systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations